EXPLORING THE INFLUENCE OF GENDER DIFFERENCES ON ATTITUDES OF YOUNG STUDENTS OF ECONOMICS TOWARD ENTERPRENEURSHIP IN SERBIA - Marčetić, Marija; Mušikić, Slađana (Ekonomija - teorija i praksa, 2022)
The main goal of this study is to investigate how gender differences affect attitudes towards entrepreneurship among students. Entrepreneurial attitudes are related to the intentions of self-employment, with the personal perception of the business environment and obstacles. The questionnaire used for data collection was adjusted to the goal of the research, the specifics of our entrepreneurial education and the economic environment in Serbia. Data were collected from 333 students of economics from the Academy of Vocational Studies in Southern Serbia. To test the initial hypotheses in this study, the following were used: descriptive-analytical method, in order to describe, evaluate and interpret the collected data, and within that, the non-parametric test χ2. Frequencies in responses between the sexes do not show discrepancies in questions involving knowledge of environment conditions, while there is a wide range in answers to questions related to personal preferences. Understanding the differences between male and female students can make it significantly easier for female students to fully use their entrepreneurial potentials, develop career preferences, and promote female entrepreneurship. New findings can help us regulate minor discrepancies in entrepreneurial education in this area.